1999
DOI: 10.1161/01.atv.19.10.2376
|View full text |Cite
|
Sign up to set email alerts
|

Two Patterns of Lipid Deposition in the Cholesterol-Fed Rabbit

Abstract: Abstract-A central feature of arterial lipid deposition is its nonuniform and variable distribution. In immature human and rabbit aortas, spontaneous lesions occur most frequently downstream of branch points, but they tend to occur upstream of the same branches at later ages. In cholesterol-fed rabbits, the juvenile pattern has been seen regardless of age. These distributions may be determined by transport properties of the arterial wall, because uptake of plasma macromolecules is elevated downstream of aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
2
29
1
3
Order By: Relevance
“…Several studies of New Zealand white rabbits fed a cholesterol-rich diet supplemented with ␣-tocopherol have reported lower TPC concentrations compared with animals consuming low levels of dietary ␣-tocopherol (57-59, 61, 70, 71, 79), although two studies reported no change in TPC concentration (54,74). In the absence of added cholesterol, ␣-tocopherol does not lower TPC (1,(75)(76)(77). In this study, the non-HDL fraction, e.g., VLDL, IDL, and LDL, underwent the greatest reduction with dietary ␣-tocopherol supplementation as has been reported in other studies (57,58,72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of New Zealand white rabbits fed a cholesterol-rich diet supplemented with ␣-tocopherol have reported lower TPC concentrations compared with animals consuming low levels of dietary ␣-tocopherol (57-59, 61, 70, 71, 79), although two studies reported no change in TPC concentration (54,74). In the absence of added cholesterol, ␣-tocopherol does not lower TPC (1,(75)(76)(77). In this study, the non-HDL fraction, e.g., VLDL, IDL, and LDL, underwent the greatest reduction with dietary ␣-tocopherol supplementation as has been reported in other studies (57,58,72).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported no change in TPC concentrations in both male and female New Zealand white rabbits (54,74). In the absence of added cholesterol, ␣ -tocopherol did not lower the TPC concentration (1,(75)(76)(77). ␣ -Tocopherol supplementation did not prevent lesion development in injured rabbit arteries but did reduce lipid peroxidation (78).…”
mentioning
confidence: 99%
“…Nuclear shape is approximately the same upstream and downstream of branches in both immature and mature mice (Bond & Weinberg 2006). Figure 9a-c shows the patterns of aortic lesion frequency around intercostal ostia in apolipoprotein E/ low-density lipoprotein receptor double knockout mice (McGillicuddy et al 2001), immature cholesterol-fed rabbits and mature cholesterol-fed rabbits (Barnes & Weinberg 1999), respectively. The comparatively uniform pattern of WSS n we found for the lowest values of Re and Q b : Q a (figure 2a) correlates with the approximate circumferential uniformity of lesion frequency seen in mice of all ages (figure 9a).…”
Section: Physiological and Pathological Relevancementioning
confidence: 99%
“…20 -22 In the present study, we examined whether the downstream distribution or a more upstream one, or a switch with age from the former to the latter, occurs in mice. We studied the origins of the intercostal arteries because these sites have been extensively studied a range of other species, because they are the only locations where age-related distributions paralleling those at human branches have been demonstrated in an animal model, 23,24 Eleven males aged 9 to 20 weeks were used in the present study. To confirm their broad similarity to the animals used in previous studies, total plasma cholesterol levels were determined in 2 mice by using a commercial enzymatic kit (Boehringer-Mannheim) and averaged 534 mg/dL.…”
mentioning
confidence: 99%
“…20 -22 In the present study, we examined whether the downstream distribution or a more upstream one, or a switch with age from the former to the latter, occurs in mice. We studied the origins of the intercostal arteries because these sites have been extensively studied a range of other species, because they are the only locations where age-related distributions paralleling those at human branches have been demonstrated in an animal model, 23,24 and because there are large numbers in each aorta. We used apoE/LDLR double-knockout mice 25 because their disease develops sufficiently quickly that it can be mapped in young animals.…”
mentioning
confidence: 99%